Satisfaction on Housing Quality in Mukim Bandar Johor Bahru and Mukim Plentong - MUSA, YANG HAZIQAH; YUSUF, ADIBAH (Trends in Undergraduate Research, 2021)
Housing study is one of the vital subjects these days as a home is a part of every person. The significance of it is undeniable because it has become one of the necessities of human life. Studies have shown that housing adequacy is connected with the Quality of Life because everything starts at home. The preceding housing problems will reflect on the policy problems of local authorities and management. Some of the previous aftermaths on housing might affect the balance and sustainability of residents. A lot of issues about housing have been drawn to the media especially in Malaysia. Water supply crisis, flood issue, a technical issue like elevator problem, waste management, security, lack of facilities such as public transport are some of the examples. It is also affecting the satisfaction towards housing quality indirectly. This study investigates the satisfaction on housing quality in Mukim Bandar Johor Bahru and Mukim Plentong, Johor Bahru, Johor which cover a total of 696,500 people. A sample of 196 respondents is surveyed to identify the locals' satisfaction with their housing quality in three aspects which are the physical of house, infrastructure, and the environment by using Cochran’s formula. Descriptive analysis is used to analyse the quantitative data obtained. The result depicts the majority of respondents (74.0%) are satisfied with their housing condition overall. Despite identifying housing quality, this study also helps to identify the problems that the locals encountered which came out from the three highest rankings on common problems. They are drainage ditch, road damage or narrow, and roof damage.